An Act for the better ordering and governing Negroes and other Slaves in this Province, and to prevent the inveigling or carrying away Slaves from their Masters or Employers, Section 28 - (:unkn) unknown (General Publisher, 1765)
Required that “any Slave” have a ticket to use a firearm that must be renewed every month.
--
Keywords: ENSLAVED PERSONS & OTHER MINORITIES